Postcolonialism, Liberal Internationalism, 9/11 and Pakistani English Fiction - Bushra Naz (University of Chitral Journal of Linguistics and Literature, 2021)
In this article I argue that Momo, Chengaze, and Daanish’s quest of political liberty and identity in Red Birds, The Reluctant Fundamentalist and Trespassing respectively manifests that liberal-internationalism is a colonial agenda. Focussing on the development of liberal internationalism because of the transformation of the colonial to a neo-colonial strategy of the powerful countries, I argue that Pakistani fiction demonstrates these policies influencing and affecting everyday life of ordinary Muslims living in refugee camps, diaspora or in Pakistan. Focal point would be the examination of the procedures and constituents of the liberal-internationalism to distinguish colonial subterfuges and ruses of upholding control in the erstwhile and contemporaneous colonies exemplified in these novels in the context of post 9/11. For the purpose of this analysis, I have taken Chris Brown and Kristen Ainley’s notion of liberal internationalism as a modern means of colonization, Gilbert Rist’s ideas of liberal internationalism as a medium of disguised colonization and E. H. Carr’s view of the internationalism as a utopian fantasy for fundamentally being a colonial economic agenda to keep afloat the conflict between ‘haves’ and ‘have not’ by way of creating an economic dependency of the third world nations’ upon the rich nations. Following this, I will interpret Brown, Ainley and Rist’s philosophy of the production of liberal internationalism as a secreted ploy of modern colonization building on Carr’s notion of international liberalism as a paradox of political and economic freedom and a disagreement against it for political and economic liberty, an essential element in M. Hanif, Mohsin Hamid, and Uzma Aslam Khan’s protagonist’s achievement of individual sovereignty through a fundamental reconceptualization of their identity to the decolonization of their personhood.